Methods for telomere length measurement: an update on current technologies and emerging approaches - Makarova, Julia A.; Belova, Uliana D.; Zvereva, Maria I.; Shkurnikov, Maxim Yu.; Tonevitsky, Alexander G. (Frontiers in Molecular Biosciences, 2025)
Telomeres are nucleoprotein complexes at chromosome ends, composed of tandemly repeated specific DNA sequences along with associated proteins. In somatic cells, telomeres progressively shorten with each cell division, making telomere length a key biomarker of cellular aging. Moreover, alterations in telomeric attrition are characteristic of numerous lifestyle factors, age-related diseases, and cancers, establishing telomere length as both a pivotal biomarker and a central focus in contemporary biomedical research. Strong interest in this area drives the continuous development of new methods for telomere length measurement and improvements to existing ones. Currently, over two dozen such methods have been developed, making the ability to select the most appropriate one essential for addressing specific research objectives. This review provides a state-of-the-art survey of all existing methods, highlighting their advantages, limitations, and applications. Special attention is focused on the rapidly evolving field of adapting long-read sequencing technologies to enhance the efficiency of telomere length measurement, along with novel insights into the structure and diversity of telomeric sequences uncovered by this approach.